Встановлення системних бар’єрів на шляху поширення корупційних практик: пріоритети сучасного суспільства - Лаврик, Г. В. (My University, 2020)
The article examines the norms and values that are shared in countries where public order with open access prevails, as well as clear requirements that oblige each state party to the United Nations Convention against Corruption to ensure institutional specialization in this area. The potential of conceptual normative provisions, values and worldviews, real institutional capacity as a kind of systemic barriers (obstacles) to the spread way of corrupt practices (networks) in modern post-socialist transformational societies, whose self-understanding includes the attraction to European civilization, is explained. They emphasizes the need for timely recourse to international standards in order to take enhanced measures to more effective and efficient corruption prevention and fight against it, which significantly destroys such a primordial tradition of interaction in society as “you to me, I to you” (“service for service ”), do ut des (“ I give so that you give ”), facio ut facias (“ I do so that you do”), and thus protects it from attraction to corrupt practices (networks). Measures in the area of prevention of corruption, which is a system of regulatory legal relations aimed at preventing corruption displays in the state by improving legal norms, legal mechanisms and measures of state influence aimed at preventing corruption as a phenomenon at different levels, are more useful than law enforcement systems, mainly criminal and administrative and legal measures aimed at bringing to justice those guilty of committing corrupt acts aimed at punishment, prevention of illegal actions and educating the population in the spirit of respect for the law, creating an atmosphere of intolerance to corruption in the state. For most of the world’s existing models (types) of specialized institutions, the system of measures covered by the fight against corruption is not decisive. Their construction and functioning is based on the realization of the desire for social order, sanctified, according to contemporaries, the achievement of prosperity and well-being, equality of opportunity and benefits, equality before the law or status, denial of privileges, freedom and justice and other values as a belief system, which prevails in society, and is the property of each individual. The state of affairs with the formation of preventive anticorruption institutions in Ukraine and institutions specializing in fighting against corruption through law enforcement measures is considered. It is proposed to determine the role of the National Agency for Prevention of Corruption in the system of state bodies of Ukraine in view of the formation of a huge demand of society for radical transformation (according to other notions consistent natural (organic) transformation), when many hopes for internal determinants of efficiency and effectiveness its activities. It is necessary to transform the current norms of legislation (rules) into wellunderstood and practically useful tools for ensuring the fair conduct of public officials, politicians, as the most important factor that determines the approximation to the relevant standards of the European Union member states. Досліджуються норми і цінності, які поділяють у країнах, де переважає суспільний порядок з відкритим доступом, а також чіткі вимоги, які зобов’язують кожну державу-учасницю Конвенції ООН проти корупції забезпечувати інституційну спеціалізацію в цій сфері. Розкривається потенціал концептуальних нормативних положень, ціннісно-світоглядних орієнтирів, справжньої інституційної спроможності як своєрідних системних бар’єрів (перешкод) на шляху поширення корупційних практик (мереж) у сучасних постсоціалістичних трансформаційних суспільствах, до саморозуміння яких належить тяжіння до європейської цивілізації. Розглядається стан справ із формуванням превентивних антикорупційних інститутів в Україні та інститутів, які спеціалізуються на боротьбі з корупційними проявами за допомогою правоохоронних заходів. Обґрунтовується необхідність перетворення норм законодавства (правил) на добре зрозумілі й практично корисні інструменти забезпечення доброчесної поведінки державних чиновників, політиків, як найважливішого чинника, який обумовлює наближення до відповідних міжнародних стандартів.
Keywords: корупційна практика; норми і цінності; інституційна спроможність; доброчесність; запобігання корупції в Україні; corruption practice; norms and values; institutional capacity; integrity; prevention of corruption in Ukraine